2006
DOI: 10.1371/journal.pcbi.0020176
|View full text |Cite
|
Sign up to set email alerts
|

DARPP-32 Is a Robust Integrator of Dopamine and Glutamate Signals

Abstract: Integration of neurotransmitter and neuromodulator signals in the striatum plays a central role in the functions and dysfunctions of the basal ganglia. DARPP-32 is a key actor of this integration in the GABAergic medium-size spiny neurons, in particular in response to dopamine and glutamate. When phosphorylated by cAMP-dependent protein kinase (PKA), DARPP-32 inhibits protein phosphatase-1 (PP1), whereas when phosphorylated by cyclin-dependent kinase 5 (CDK5) it inhibits PKA. DARPP-32 is also regulated by case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 59 publications
(58 reference statements)
4
125
0
2
Order By: Relevance
“…A more detailed picture of the allowed states of phosphorylation of DARPP-32 (the ''DARPP-32 subnetwork'') is shown in Because much is understood about the composition of the DARPP-32 signaling cascade, it is a natural setting for computational studies. Recently, for example, two groups have simulated aspects of the network to study the effect of transient Ca 2ϩ and dopamine (or cAMP) signals on DARPP-32 phosphorylation (21,22). In both cases, the authors found interesting, time-dependent features of the pathway.…”
Section: The Darpp-32 Cascadementioning
confidence: 99%
“…A more detailed picture of the allowed states of phosphorylation of DARPP-32 (the ''DARPP-32 subnetwork'') is shown in Because much is understood about the composition of the DARPP-32 signaling cascade, it is a natural setting for computational studies. Recently, for example, two groups have simulated aspects of the network to study the effect of transient Ca 2ϩ and dopamine (or cAMP) signals on DARPP-32 phosphorylation (21,22). In both cases, the authors found interesting, time-dependent features of the pathway.…”
Section: The Darpp-32 Cascadementioning
confidence: 99%
“…Phospholipase C activates Calmodulin that elevates Calcium. Also D2 receptor triggered processes converge on DARPP32 (dopamine and cAMP regulated phosphoprotein 32) out by the studies [23,44] . The computer simulation of the model shows, that a brief dopamine pulse is transformed into a saw-tooth like signal on the level of proteinkinase A (PKA;…”
Section: Modeling Cellular Processes -The Dynamics Of the Intracellulmentioning
confidence: 95%
“…Indeed, PSD proteins such as DARPP-32 and the Ca(2+)/calmodulin kinase type II (CaMKII) are pivotal biochemical bridges between dopamine and glutamate signaling pathways [147,148]. Moreover, molecules such as protein kinase B (Akt), glycogen synthase kinase-3β (GSK-3β), and extracellular signal-regulated kinase (Erk) are involved in both dopamine and glutamate signaling cascades at the post-receptor level and interact with PSD molecules [2,[149][150][151][152][153].…”
Section: Dopamine-glutamate Interplay At the Psd And Related Mirnas Amentioning
confidence: 99%